Fine-Needle Aspiration Cytology Is an Alternative Source of High Quality Archival Samples in Biobanking. (29th June 2011) - Malami, Sani Abubakar
Abstract : Advances in fine-needle aspiration cytology (FNAC) techniques allows for a whole range of procedures on these limited sources of tissue. Where fresh aspirates are not readily available, archival FNAC samples had also been used for clinical diagnoses, molecular profiling, and disease monitoring with impressive results. Nonetheless, legitimate concerns exist regarding the reliability of these banked specimens. Increased demands on human tissues in response to the rapid acceleration on emerging scientific platforms will probably make tissue bank creation derived from archival FNAC a priority. To highlight its future prospects as a resource for tissue banking, this paper provides an overview of the use of archival FNAC in clinical situations and ancillary studies. It is concluded that tissue banks of archival FNAC specimens might have great promise in optimizing patient care and translational research.